The effective promotion of informal control in information systems offshoring projects - Wiener, Martin; Remus, Ulrich; Heumann, Jakob; Mähring, Magnus (European journal of information systems, 2015)
As firms increasingly engage in interorganizational information systems (IS) projects, including IS offshoring projects, the challenge for client firms of effectively exercising control across organizational boundaries becomes critical. Although the importance of informal controls (clan and self-control) in this context has been recognized, prior research has focused primarily on formal controls. Consequently, our understanding of the use of clan and self-control in interorganizational IS projects is scarce, and partly inconsistent or contradictory. This study focuses the client's role in promoting informal controls in interorganizational projects involving distant client-vendor relationships as well as the effectiveness of such controls. We use matched-pair survey data from 86 IS offshoring projects involving client and vendor relationship managers. Our results show an interesting pattern: while clan control is considerably more difficult to promote than self-control in client-vendor project relationships, only clan control has a direct positive impact on project performance. Moreover, formal control modes, national cultural values, and project context factors moderate both the promotion and the effectiveness of informal controls. Our study's main contributions lie in establishing the relevance of the distinction between informal control given and received, and the importance of the client's role in promoting informal controls.